2019
DOI: 10.1177/0974910119887241
|View full text |Cite
|
Sign up to set email alerts
|

Mergers and Acquisitions Antecedents in BRICS

Abstract: This study proposes merger and acquisitions (M&A) antecedents’ model using observations from BRICS countries. It is expected that BRICS countries will remain a hotbed of M&A activity in the future and hence by analyzing BRICS research, we seek to provide a deeper insight into the current state of research, outline new insight, and propose future directions. Using a systematic literature review (SLR) method, we found that antecedents including top leadership role, self-interest of managers, targeted fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…As the largest economy shifting from a central system to a market‐based economy, China provides the best case study for this research as the development in the country is uneven due to disparities in regional and sociocultural differences across locations. Moreover, China's remarkable economic growth attributable to firms activities such as M&A over the last four decades is worth investigating (Opoku‐Mensah, Yin, Sandra, & Tuffour, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As the largest economy shifting from a central system to a market‐based economy, China provides the best case study for this research as the development in the country is uneven due to disparities in regional and sociocultural differences across locations. Moreover, China's remarkable economic growth attributable to firms activities such as M&A over the last four decades is worth investigating (Opoku‐Mensah, Yin, Sandra, & Tuffour, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended that firms, especially those who intend to make acquisitions, develop stronger ties to enjoy some governments' benefits. In the Chinese business environment, having stronger business ties with government officials is a great asset a firm can possess as the term “guanxi” is commonly used to describe such a relationship (Opoku-mensah et al , 2021).…”
Section: Conclusion Implication and Future Workmentioning
confidence: 99%
“…Management and business studies have identified factors such as strategic fit (Cornaggia and Li, 2019;Lee et al, 2018;Olcay et al, 2019), lack of due diligence during the preacquisition stage (Wangerin, 2019;Bi et al, 2020;Kumar and Sengupta, 2020) and challenges during the integration stage (Figueira et al, 2020;Kumar and Sengupta, 2020) as the contributors to M&A synergy creation. Finance and economics literature have identified how managers' characteristics such as chief executive officer's (CEO) traits, compensations, multiple directorships, board composition, political factors, financing sources and CSRrelated policies influence M&A success (Opoku-Mensah et al, 2019;Renneboog and Vansteenkiste, 2019).…”
Section: Literature Review 21 Determinants Of Merger and Acquisition ...mentioning
confidence: 99%
See 1 more Smart Citation
“…listed companies EDCON (Businesstech 2020) and Group 5 (Creamer Media 2021) are striking examples. However, little is known about African mergers and acquisitions (Angwin et al 2016) and, specifically, those in South Africa (Opoku-Mensah et al 2019). In Europe, executing business rescue through a going concern sale requires (1) a bidding process, (2) a tool to leave debt behind (asset deal free and clear or share deal in a restructuring plan) and (3) a tool to test the agreed price, such as court scrutiny of the bidding process or creditor approval (Wessels & Madaus 2018).…”
Section: Introductionmentioning
confidence: 99%